2015
DOI: 10.1093/epirev/mxu006
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and Violent Behavior Among Military Personnel Deployed to Iraq and Afghanistan: Prevalence and Link With Deployment and Combat Exposure

Abstract: A systematic review and meta-analyses were conducted on studies of the prevalence of aggressive and violent behavior, as well as of violent offenses and convictions, among military personnel following deployment to Iraq and/or Afghanistan; the relationship with deployment and combat exposure; and the role that mental health problems, such as post-traumatic stress disorder (PTSD), have on the pathway between deployment and combat to violence. Seventeen studies published between January 1, 2001, and February 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 69 publications
6
107
3
Order By: Relevance
“…Second, our finding that never-deployed and previously-deployed soldiers had comparably elevated violent crime risk is striking given that recent research has suggested that combat exposure leads to increased violence among soldiers returning from deployment (MacManus et al , 2015). That the RF analysis failing to find evidence of meaningful interactions means that no evidence was found for differences in the strength of associations of predictors among the previously-deployed and never-deployed versus the currently-deployed.…”
Section: Discussionmentioning
confidence: 74%
“…Second, our finding that never-deployed and previously-deployed soldiers had comparably elevated violent crime risk is striking given that recent research has suggested that combat exposure leads to increased violence among soldiers returning from deployment (MacManus et al , 2015). That the RF analysis failing to find evidence of meaningful interactions means that no evidence was found for differences in the strength of associations of predictors among the previously-deployed and never-deployed versus the currently-deployed.…”
Section: Discussionmentioning
confidence: 74%
“…Many service members who have been previously deployed experience other mental health conditions or cognitive impairments, such as TBI and related psychiatric comorbidities (Carlson et al, 2010). Additionally, other factors that may also be associated with deployment-such as high propensities of risktaking, impulsivity, and anger (MacManus et al, 2015)-can be indicators of other mental health problems and adverse health-related behaviors, such as suicide ideation and attempts (Hawton et al, 2003;Novaco et al, 2012). Serious mental illnesses often trigger long-term negative health and social outcomes, such as marital instability and even homelessness, and understanding the long-term effects of deployment and combat exposure on mental health is vital to reducing such negative outcomes.…”
Section: Deployment and Mental Healthmentioning
confidence: 99%
“…Violence perpetration among veterans has emerged as a critical public health concern (MacManus et al, 2015; Sontag and Alvarez, 2008). To date, however, there has been relatively little research investigating factors related to violence among veterans in VA mental health treatment.…”
Section: Introductionmentioning
confidence: 99%